Contributing or free-riding? Voluntary participation in a public good economy - Hideo Konishi; Taiji Furusawa (Theoretical Economics, 2011)
We consider a (pure) public goods provision problem with voluntary participation in a quasi-linear economy. We propose a new hybrid solution concept, the free-riding-proof core (FRP-Core), which endogenously determines a contribution group, public goods provision level, and how to share the provision costs. The FRP-Core is always nonempty in public goods economies but does not usually achieve global efficiency. The FRP-Core has support from both cooperative and noncooperative games. In particular, it is equivalent to the set of perfectly coalition-proof Nash equilibria (Bernheim, Peleg, and Whinston, 1987) of a dynamic game with players' participation decisions followed by a common agency game of public goods provision. We illustrate various properties of the FRP-Core with an example. We also show that the equilibrium level of public goods shrinks to zero as the economy is replicated.
Keywords: H41; C71; C72; D61; D72; 330; Endogenous coalition formation; externalities; public good; perfectly coalition-proof Nash equilibrium; free riders; free-riding-proof core; lobbying; common agency game